Persistence of infectivity in elderly individuals diagnosed with severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection 10 days after onset of symptoms: A cross-sectional study. (6th April 2023) - Longtin, Yves; Parkes, Leighanne O.; Charest, Hugues; Rajarison, Stacy; Zaharatos, Gerasimos J.; Fafard, Judith; Roger, Michel; De Serres, Gaston
Abstract: We performed viral culture of nasopharyngeal specimens in individuals aged 79 and older, infected with severe acute respiratory coronavirus virus 2 (SARS-CoV-2), 10 days after symptom onset. A positive viral culture was obtained in 10 (45%) of 22 participants, including 4 (33%) of 12 individuals with improving symptoms. The results of this small study suggest that infectivity may be prolonged among older individuals.